2006
DOI: 10.1037/0012-1649.42.4.656
|View full text |Cite
|
Sign up to set email alerts
|

Reticent behavior and experiences in peer interactions in Chinese and Canadian children.

Abstract: In this study, the authors examined relations between reticent behavior in unfamiliar peer situations and experiences in interactions in Chinese and Canadian children. Observational data were collected from samples of children at 4 years of age in the People's Republic of China and Canada. The results indicated that relations between reticent behavior and peer initiations were similar in the 2 samples. The differences between the samples were mainly in peer responses. Reticent behavior was associated with peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
104
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 48 publications
5
104
0
6
Order By: Relevance
“…Diversos estudos têm vindo a salientar possíveis diferenças no modo e grau em que este fenómeno é interpretado como um defi cit em diferentes culturas (e.g., Chen et al, 2006;Chen et al, 2004). Por exemplo, nas culturas asiáticas pais e professores tendem a avaliar a timidez e a inibição de modo mais positivo e estas crianças parecem não se encontrar em situação de risco no seu grupo de pares (e.g., Chen et al, 1998;Chen, Rubin, & Li, 1995), contrariamente ao que se verifi ca nas amostras anglo-saxónicas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Diversos estudos têm vindo a salientar possíveis diferenças no modo e grau em que este fenómeno é interpretado como um defi cit em diferentes culturas (e.g., Chen et al, 2006;Chen et al, 2004). Por exemplo, nas culturas asiáticas pais e professores tendem a avaliar a timidez e a inibição de modo mais positivo e estas crianças parecem não se encontrar em situação de risco no seu grupo de pares (e.g., Chen et al, 1998;Chen, Rubin, & Li, 1995), contrariamente ao que se verifi ca nas amostras anglo-saxónicas.…”
Section: Discussionunclassified
“…Quando estas crianças procuram iniciar interações, tendem a ser pouco efi cazes, utilizando estratégias menos assertivas e mais indiretas/subtis, comparativamente com os seus pares mais sociáveis, sendo frequentemente ignoradas ou mesmo rejeitadas nestas iniciativas (eg., Chen, DeSouza, Chen, & Wang, 2006;Rubin, Daniels-Bierness, & Bream, 1984;Rubin & Rose-Krasnor, 1986). Tendem, ainda, a ter valores de aceitação sociométrica mais baixos (Hart et al, 2000) e a ser escolhidas, como as crianças, com as quais os seus pares menos gostam de brincar (eg., Gazelle & Ladd, 2003;Rubin, Chen, & Hymel, 1993).…”
unclassified
See 1 more Smart Citation
“…In societies where assertiveness and self-expression are not highly appreciated or encouraged, reticent behavior is likely to be viewed as less deviant and maladaptive. Chen et al (2006) found that, compared with their counterparts in North America, peers in China were more accepting and supportive of reticent children by showing approval and cooperation to social initiations of reticent children and maintaining interactions with them. In traditional Chinese society, behavioral vigilance and wariness have been positively evaluated, which may promote the social endorsement of children's reticence (Chen 2010).…”
Section: Chinese Background and Children's Social Reticence And Solitmentioning
confidence: 95%
“…Even in early childhood, peers respond to shy behaviors with exclusion, rejection, and victimization (e.g., Chen, DeSouza, Chen, & Wang, 2006 ;Gazelle & Ladd, 2003 ;Hart et al, 2000 ;Perren & Alsaker, 2006 ). Moreover, with increased age, social withdrawal becomes increasingly concurrently and predictively associated with peer exclusion and rejection (e.g., Newcomb, Bukowski, & Pattee, 1993 ;Oh et al, 2008 ).…”
Section: Rejection and V Ictimizationmentioning
confidence: 99%